Persona Manifestasi Diri pada Lirik Lagu dalam Album Ini Bukan Nosstress Karya Nosstress: Kajian Estetika - Pangesti, Shafa; Purnomo, Mulyo Hadi; Fadilah, Yuniardi (Wicara: Jurnal Sastra, Bahasa, dan Budaya, 2024)
The purpose of this study is to reveal the form of manifestation through aesthetic means in the lyrics in the album Ini Bukan Nostress by Nosstress. This qualitative descriptive study uses an objective method with listening and noting techniques. The data taken is in the form of three of the nine song lyrics in the album. The results of this study are the discovery of aesthetic concepts through the perception of meanings depicted by the lyrical "I". The results of this perception produce aesthetic values that can be reflected as an aesthetic experience. The existence of self-manifestation based on the interpretation of the law of attraction in the three songs in the album Ini Bukan Nostress is a means to evaluate oneself through the beauty depicted from the intrinsic elements. Elements such as diction, imagery, and the use of rhyme in the lyrics can emphasize hope, optimism, and determination.